ANALYSIS OF QUR’ANIC READING ABILITY BASED ON TAJWEED AMONG ELEVENTH GRADE STUDENTS AT MA ANNAQSYABANDIYAH NW GELANGGANG - Wawan Efendi Ahmad (Indonesian Journal of Education and Science, 2024)
This study investigates the challenges encountered by Grade XI students at MA Annaqsyabandiah NW Gelanggang in reading the Qur'an, focusing on their application of tajweed principles. The research aims to understand specific difficulties in articulation, letter characteristics, length and duration of recitation, and the rule of idgham bigunnah. Employing qualitative methods, data were gathered through observation and interviews with students and teachers. The findings reveal that teachers address these issues through three main strategies: the Tahsin method, which emphasizes correct articulation; habitual practice, encouraging regular recitation; and the listening method, allowing teachers to assess and correct individual errors. These approaches have significantly improved students' Qur'anic recitation abilities. The study concludes that teacher-led, tajweed-focused methods are essential in overcoming recitation difficulties, with implications for enhancing Qur'anic literacy in educational institutions. Recommendations for further research include exploring additional instructional methods and technology-assisted learning tools.